Citation patterns, the Matilda effect and gender bias in communication & media Studies scientific output in Ibero-America (1980-2022) (Communication & Society, 2025)
This article analyses diachronically the role of women in the field of communication & media studies in Ibero-America by studying the presence or absence of women in the bibliography of a selection of articles taken from 60 communication academic journals in 9 countries (Spain, Portugal, Brazil, Argentina, Mexico, Chile, Colombia, Ecuador and Peru) between 1980 and 2022. This study measures the degree of visibility of female scientists and their contribution and compares it statistically to that of their male counterparts by quantifying from a gender perspective the citation patterns of authors of the 484 scientific articles included in the study. The findings showed that the visibility of the female researchers-authors increased over time. Furthermore, an over-citation of publications by male researchers was also found. Last, in one of the periods analysed, in the years between 1996-2010, gender homophily was found, i.e., female researchers tended to cite more women than men during this period.